Association between diverticular disease requiring surgical intervention and mortality in the postlung transplant population ‐ a retrospective cohort study. (25th March 2019) - Tague, Laneshia K.; Adams, William; Young, Katherine A.; Kwon, Oh Jin; Mahoney, Erin; Lowery, Erin M.
Summary: Lung Transplant recipients are at increased risk of complicated diverticular disease. We aim to assess the rate of diverticular surgery in a postlung transplantation population and identify risk factors for surgery. We performed a retrospective cohort study of lung transplant recipients from 2007 to 2011. Demographic variables were evaluated with the Mann–Whitney U and chi‐squared tests. Cox regression was performed to evaluate 1‐ and 2‐year landmark survival, assess predictor variables of diverticular surgery and evaluate impact of surgery on CLAD development. Of 17 of 158 patients (10.7%) underwent diverticular‐related surgery. Surgical patients had significantly worse survival than nonsurgical patients at 1 year [aHR 2.93 (1.05–8.21), P = 0.041] and 2 year [aHR 4.17 (1.26–13.84), P = 0.020] landmark analyses. Transplant indication of alpha‐1 antitrypsin disease and cystic fibrosis were significantly associated with the need for diverticular surgery. Emergent surgery was associated with poorer survival [aHR 5.12(1.00–26.27), P = 0.050]. Lung transplant patients requiring surgery for complicated diverticular disease have significantly poorer survival than those who do not require surgery. Surgery was more common in patients transplanted for A1AT and CF. Optimal assessment and risk stratification of diverticular disease is necessary to prevent excessive morbidity and mortality following transplantation.